Molecular Detection and Subtyping of Human Blastocystis and the Clinical Implications: Comparisons between Diarrheal and Non-diarrheal Groups in Korean Populations - Kim, Moon-Ju; Won, Eun Jeong; Kim, Soo Hyun; Shin, Jong Hee; Chai, Jong-Yil (Korean journal of parasitology, 2020)
Blastocystis has recently been recognized as the most common eukaryotic microbe of the human gut. We investigated the prevalence of Blastocystis and their subtypes in diarrheal and non-diarrheal groups and the associated clinical parameters. A total of 324 stool samples were obtained from 196 diarrheal and 128 non-diarrheal subjects. Blastocystis subtypes were determined by sequencing the small subunit ribosomal DNA (SSU rRNA) gene. Demographic, clinical and laboratory data were collected and analyzed by diarrhea and Blastocystis status. The overall rate of Blastocystis positivity was 9.0% (29/324) but was significantly higher in the non-diarrheal group (18.0% vs. 3.1%, P<0.0001). Of the 6 Blastocystis-positive diarrheal patients, 3 (50.0%), none (0.0%), 2 (33.3%), and 1 (16.7%) were infected with subtypes ST1, ST2, ST3, and multiple subtypes, respectively. Of the 23 Blastocystis-positive non-diarrheal patients, 4 (17.4%), 1 (4.3%), and 18 (78.3%) were infected with subtypes ST1, ST2, and ST3, respectively. Blastocystis was less common in the diarrheal than the non-diarrheal group (odds ratio, 0.144; 95% confidence interval, 0.057–0.365, P<0.001). Of the 3 subtypes, ST3 was more frequently observed in the non-diarrheal than diarrheal group (78.3% vs. 33.3%, P=0.0341). Collectively, Blastocystis was found in both the diarrheal and non-diarrheal groups and ST3 was the most common subtype in Korea.